Patrones de actividad de forrajeo de Pogonomyrmex barbatus en el valle semiárido intertropical de Zapotitlán Salinas, Puebla - Guzmán Mendoza, Rafael (Universidad Autónoma Metropolitana, 2004)
The foraging patterns of Pogonomyrmex barbatus were studied under conditions of high and low plant cover and diversity. Results showed that the trophic niche breadth is influenced by a relationship between abundance and diversity of available resources in the habitat. The highest observed niche breadth is not necessarily correlated with conditions of low resource abundance as the optimal foraging hypothesis states. The idea that deserts are highly heterogeneous environments at small spatial and temporal scales is supported by the observed differences in the dynamics of resources abundance and diversity among the studied sites. The broad generalist foraging habit of P. barbatus indicates that it is intricately embedded inside the desert trophic web. So, this species assumes different ecological roles, becoming an important pathway in the terrestrial ecosystems flux of energy.; Fue estudiado el patrón de forrajeo de Pogonomyrmex barbatus en dos ambientes contrastantes en cuanto a diversidad y cobertura vegetal. Los resultados muestran que la amplitud de nicho trófico se ve afectado por una relación entre la abundancia y diversidad de los recursos disponibles en el hábitat, donde el mayor grado de amplitud no necesariamente corresponde con situaciones donde hay poca abundancia de recursos como lo señala la hipótesis del forrajeo óptimo. La dinámica de abundancia y diversidad de recursos fue diferente en cada sitio lo que apoya la idea de que los desiertos son ambientes muy heterogéneos a escalas espaciotemporales pequeñas. El amplio habito alimenticio generalista de estas hormigas indica que están inmersas de manera intrincada dentro de la red trófica, asumiendo diferentes papeles ecológicos y siendo una vía importante en el flujo de energía de los ecosistemas terrestres.